Resistin associated with higher cardiovascular events in intermediate grace score of acute coronary syndrome - Rizki Amalia Gumilang; Nahar Taufiq; Budi Yuli Setianto (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2021)
Previous studies revealed that inflammatory biomarkers have a role in the clinical outcomes of acute coronary syndromes (ACS) and also in prediction of cardiovascular events using GRACE score. Resistin, a recently identified inflammatory biomarker, also has a role in clinical outcomes of ACS but its role related to GRACE score risk stratification is unknown. Three risk stratifications of ACS based on GRACE scores were used i.e. low, intermediate, and high. Some studies reported that inflammatory biomarkers have a role in cardiovascular events of patients with low risk GRACE scores, but their role in the patients with intermediate risk still needs to be elucidated. This study aimed to investigate the role of resistin in cardiovascular events of ACS patients with intermediate risk GRACE score. This was an observational study using a cross-sectional design involving sixty-three patients with ACS who fulfilled the inclusion and exclusion criteria. Blood samples were drawn 24 h after onset. Resistin level was analyzed and classified according to its median values. The cardiovascular event was defined as mortality, ischemic events, acute heart failure or arrhythmia during hospitalization. The result showed that cardiovascular events were significantly higher in patients with resistin levels higher than median i.e. 23.8% compared to those with resistin levels similar or lower than median i.e. 11.1% (OR 3.348, 95%CI: 1.125-10.007 p=0.027). It can be concluded high resistin level is associated with an increase of cardiovascular events of ACS with intermediate risk GRACE score.